Realism and Eroticism: Re-Reading Bazin - Quigley, Paula (My University, 2013)
Bazin s distinction between different kinds of realism discriminates between an authentic mode of apprehension and mere sight, or between revelation and spectacle, as it were, where spectacle, significantly, is connected with the arousal of physical sensation. My argument is that this resonates in unexpected ways with a 'modernist' conceptual paradigm, specifically in relation to the persistent prioritization of the temporal over the spatial as the superior aesthetic register, itself based upon a residual resistance to the visual realm. To pursue this, I shall return to some of Bazin s most influential texts and concepts. In addition, a consideration of his more marginal discussions of cinema, sex and censorship will offer an oblique entry point into some of these broader issues at play in his work.
PUBLISHED
Keywords: André Bazin, Gotthold Lessing, realism, pseudorealism, modernism, film theory; Creative Technologies